Platelet Aggregation Test on Different Dual Antiplatelet Strategies in Acute Coronary Syndrome - Amalia, Yustisia; Hernaningsih, Yetti; Yusuf, Moch; Indrasari, Yulia (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Acute coronary syndrome (ACS) is frequently accompanied by platelet hyper-aggregation, which requires percutaneous coronary intervention (PCI) as definitive management, as it has the side effect of thrombosis, so platelet function must be monitored. This study aimed to evaluate platelet aggregation between the loading and maintenance doses of different DAPT combinations in patients with ACS undergoing PCI. This study employed a prospective cohort design with consecutive sampling, conducted at Dr. Soetomo General Academic Hospital in Surabaya and Universitas Airlangga Hospital in Indonesia. Patients with active bleeding, hemodynamic instability, or contraindications to antiplatelet agents were excluded. Patients were divided into a high-risk bleeding ACS group treated with aspirin–clopidogrel and a low-risk bleeding ACS group treated with aspirin–ticagrelor or aspirin–prasugrel according to the ARC-HBR score. Platelet aggregation tests (% maximum aggregation) were performed using the light transmission aggregometry method with adenosine diphosphate (ADP), collagen (COL), and epinephrine (EPI) agonists. Statistical analysis was performed to compare the differences between groups.The study included a total of 68 ACS patients with PCI: aspirin–clopidogrel (22.1%), aspirin–ticagrelor (44.1%), and aspirin–prasugrel (33.8%). There was no significant difference in platelet aggregation between groups with EPI and COL agonists. ADP agonists showed a significant difference between the loading and maintenance doses in the aspirin–ticagrelor and aspirin–prasugrel groups. The most important difference was observed in the aspirin–prasugrel group (95% CI: -22.68, -9.00; p = 0.000). Aspirin–prasugrel is the most potent inhibitor of platelet aggregation in patients with ACS undergoing PCI.